2020
DOI: 10.4194/1303-2712-v21_1_05
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Squid Pen Chitooligosaccharide and High Voltage Cold Atmospheric Plasma on the Quality of Asian Sea Bass Slices Inoculated with Pseudomonas aeruginosa

Abstract: The effects of chitooligosaccharide (COS) at different concentrations (0.05, 0.1 and 0.2%, w/w) without and with the application of high voltage cold atmospheric plasma (HVCAP) at different ratios of argon (Ar) and oxygen (O2), 90%Ar/10%O2 and 80%Ar/20%O2 on the growth of Pseudomonas aeruginosa inoculated (6 log CFU/mL) on Asian sea bass slices were monitored for 0 and 24 h incubation at 4ºC. Impact of COS on the changes in lipid and protein oxidation caused by HVCAP was also determined. All the HVCAP treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Some researchers reported an additive effect by using different gas compositions (air, nitrogen, oxygen, argon, etc.) at different pressures for different time intervals, singly or in combination, for plasma generation and packaging types [34], or by pre-treating with chitooligosaccharides [35]; the NTAP effects were further enhanced in terms of microbial destruction and attributed to further diversification in the generation of reactive species.…”
Section: Non-thermal Atmospheric Plasma (Ntap)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers reported an additive effect by using different gas compositions (air, nitrogen, oxygen, argon, etc.) at different pressures for different time intervals, singly or in combination, for plasma generation and packaging types [34], or by pre-treating with chitooligosaccharides [35]; the NTAP effects were further enhanced in terms of microbial destruction and attributed to further diversification in the generation of reactive species.…”
Section: Non-thermal Atmospheric Plasma (Ntap)mentioning
confidence: 99%
“…The main limitation observed in almost all case studies analysed was lipid oxidation, which increases exponentially as exposure time and energy used raise; this can lead to the creation of short-chain fatty acids, aldehydes, acid hydroxides and ketoacids, thus causing off-flavours and off-odours during storage. However, some recent investigations found that pre-treatment of fish products with natural extracts rich in antioxidants could retard the rate of lipid oxidation in samples treated with NTAP [25,26,[33][34][35].…”
Section: Non-thermal Atmospheric Plasma (Ntap)mentioning
confidence: 99%
“…HVCP generates several reactive species (RESPE) including reactive nitrogen species (RNS) as well as reactive oxygen species (ROS) such as peroxide, nitrogen oxides (NxOy), singlet oxygen, and ozone, which are responsible for their excellent bacteria inhibition [11]. Nevertheless, RESPE have been documented to induce the oxidation of lipid and protein in seafood [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The decline in PV was noticeable after day 12 until the end of storage. This was most likely due to the decomposition of unstable hyperperoxides to other components (Singh et al, 2021a). On day 15, PV was not different between samples wrapped with CS/CE conjugate composite film, irrespective of the packaging atmosphere.…”
Section: Microbial Countsmentioning
confidence: 86%
“…However, various factors including enzymatic and biochemical reaction, lipid oxidation and microbial contamination are considered as the principal contributors to quality deterioration and limited shelf-life of ASB during post-harvest handling and storage (Chaijan et al, 2006). To enhance shelf-life of seafood and impede the rate of biochemical and microbial activities, use of natural additives including chitosan (CS) with or without non-thermal processing techniques have been gaining attention instead of synthetic preservatives, which cause adverse effect or risk to human health (Singh et al, 2021a, Mittal et al, 2021b.…”
Section: Introductionmentioning
confidence: 99%